Building new discrete supramolecular assemblies through the interaction of iso-tellurazole N-oxides with Lewis acids and bases. (21st July 2017) - Ho, Peter C.; Jenkins, Hilary A.; Britten, James F.; Vargas-Baca, Ignacio
Abstract : The supramolecular macrocycles spontaneously assembled by iso-tellurazole N-oxides are stable towards Lewis bases as strong as N-heterocyclic carbenes (NHC) but readily react with Lewis acids such as BR3 (R = Ph, F). The electron acceptor ability of the tellurium atom is greatly enhanced in the resulting O-bonded adducts, which consequently enables binding to a variety of Lewis bases that includes acetonitrile, 4-dimethylaminopyridine, 4, 4′-bipyridine, triphenyl phosphine, a N-heterocyclic carbene and a second molecule of iso-tellurazole N-oxide.